Comparison of Strength Between Laterite Soil and Clay Compressed Stabilized Earth Bricks (CSEBs) - Abdullah Abd Halid; Nagapan Sasitharan; Antonyova Anna; Rasiah Kannan; Yunus Riduan; Sohu Samiullah (MATEC Web of Conferences, 2017)
Compressed Stabilized Earth Brick (CSEB) is a sustainable material utilizing locally available soils mixed with stabilizers to increase its strength. Two main factors affecting the strength of prototype are its compressive strength and water absorption rate. In this study, the mix proportion ratio for producing CSEB prototypes from laterite soil and clay types was 1:10 (cement:soil). Three different compactions (i.e. 2000, 3000, and 4000 Psi) were applied to produce prototypes with dimension of 100×50×40 mm. The samples were tested at the ages of 7 and 28 days. For laterite soil CSEB, the optimum strength was achieved by the sample subjected to 2000 Psi compaction,withits compressive strength of 9.0 N/mm2 and water absorption rate of 14.9%. For clay CSEBthe optimum strength observed was the sample subjected to 4000 Psicompaction, with the compressive strength of 5.8 N/mm2 and water absorption rate of 17%. However, the compressive strength of clay CSEB is still below the level specified in the MS 76:1972, which is over 7 N/mm2 for the load-bearing fired brick Class (1). This study also revealed that the increased in compression pressure would result in different strength performances for both CSEBs made from laterite soil and clay.